Bumble bee colony health and performance vary widely across the urban ecosystem. Issue 10 (24th August 2022) - Theodorou, Panagiotis; Kühn, Olga; Baltz, Lucie M.; Wild, Christopher; Rasti, Sirus Leonard; Bucksch, Carolina Ruiz; Strohm, Erhard; Paxton, Robert J.; Kurze, Christoph
Abstract: Urbanization is a global phenomenon that can affect fitness and could challenge the persistence of most species, including wild bee pollinators. Yet, how and which environmental features affect bee health and fitness within the urban ecosystem remain unclear. Here, we placed experimental Bombus terrestris colonies in sites spanning from the edge into a city's core to investigate bumble bee parasitism, foraging behaviour, energetic stress, colony growth and reproductive output. In each site, ambient temperature was recorded, the availability of floral resources was evaluated and landscape heterogeneity was characterized using land‐cover maps. We found that Bombus terrestris parasitism levels increased across the season in line with colony growth but were negatively related to the proportion of impervious surfaces surrounding a site. Bombus terrestris foraging trip duration decreased with increasing ecotones (edge density) but, conversely, increased in sites with honey bee hives present. Energetic stress was evaluated as lowered trehalose titre in the haemolymph of returning foragers; stress increased with the proportion of impervious surfaces. Furthermore, our analyses identified ambient temperature to be a strong predictor of Bombus terrestris colony performance in that high ambient temperature reduced colony growth and indirectly the production of sexual offspring (gynes). Our results highlight the importance of ecotones as well as minimizing the intensity of urbanization and urban honey bee beekeeping for bumble bee colony health and foraging behaviour. They also point to the importance of microclimate (i.e. temperature) for bumble bee colony performance and suggest that increasing temperatures could have a negative impact in slowing colony weight gain, and indirectly in reducing colony reproduction. Abstract : Urbanization can affect species diversity. Yet, whether urbanization affects fitness remains largely neglected. This experiment using bumblebee colonies reveals strong relationships between temperature and landscape‐scale drivers and colony health, performance and reproductive success, suggesting that environmental heterogeneity within the urban ecosystem impacts bumblebee colonies